Conflict of Authorship:Corporate Body Vs Corporate Body - Ranganathan, S. R.; Bhattacharya, G. (Journal of Information and Knowledge, 1989)
A conflict of authorship should get resolved at the stage of the definition of the term 'Author' and of the terms denoting the different kinds of author. In the case of the conflict "Corporate Body vs Corporate Body, each of the initial Formal Definitions requires to be propped up by an appropriate Interpretative Definition as a sequel to it. Many of the Cataloguing Codes do not give an explicit Interpretative Definition. But they are implied in their rules for Choice and Rendering of Heading; and they can be distilled out of these rules. A critical and comparative study of how RDC and the different editions of AACR and of CCC resolve the conflict "Corporate Body vs Corporate Body" is made on the basis of the relevant Interpretative Definitions - either explicitly stated or distilled out from the rules implying them. Conflicts centring round the following kinds of Corporate Bodies are considered: (1) Government; (2) Near Sovereign Body; (3) Quasi Government; (4) Institution; and (5) Conference. A separate part is devoted to each kind of Corporate Body. Each part begins with a section on Terminology giving the precise definitions of the terms needed to develop the ideas systematically. The specific issues considered generally in relation to each kind of Corporate Body are: (1) Whole Corporate Body vs its Organ of Remove 1; (2) Organ of Remove 1 vs Organ of Remove 2; (3) Corporate Body vs its Quasi Independent Institution; (4) Corporate Body vs Its Organ Conference; and (5) Corporate .Body as a Delegated-from-Body vs Conference: Impact, if any,  received by any Code from the earlier Codes, is indicated. Wherever necessary, the Interpretative Definitions for inclusion in CCC (Ed 6) are given.